ДИНАМИЧЕСКИЕ СВОЙСТВА ЧАСТОТНО-ФАЗОВЫХ ЛАЗЕРНЫХ ДАЛЬНОМЕРНЫХ СИСТЕМ С ЦИФРОВЫМИ СИНТЕЗАТОРАМИ ЧАСТОТЫ - Брагинец, И.А.; Зайцев, Е.А.; Латенко, В.И.; Орнатский, И.А.; Логвиненко, И.В. (Інститут електродинаміки НАН України, Київ, 2013)
The single-channel frequency-phase system, focused on the use in the laser measurer of displacement and vibration parameters is considered. Laser emitter voltage is generated using a digital frequency synthesizer, and informative parameters of the system are determined by multiplying the voltage of the investigated signal and heterodyne with subsequent digital processing. It is shown that these devices have the dynamic error wich is determined, mainly, by the ratio of synthesizer and of frequency of the investigated signal. The value of this error with ratio to different frequencies, depending on the measuring time of the signal are determinated. References 8, figures 6.